Assessing Factors Influencing Technology Adoption for Online Purchasing Amid COVID-19 in Qatar: Moderating Role of Word of Mouth - Al Halbusi, Hussam; Al-Sulaiti, Khalid; Abbas, Jaffar; Al-Sulaiti, Ibrahim (Frontiers in Environmental Science, 2022)
The COVID-19 pandemic developed new challenges for global consumers. In response to this disaster, digital technology users have faced the necessity to adopt and use specific technology apps for online shopping. This article examines how contingencies disrupt existing theoretical models and their implications for the post-COVID-19 era for online purchases. Customers prefer apps to use on the websites for search and purchase amid the COVID-19 crisis. The websites offer competitive advantages to apps for branding and CRM prospects. This motive keeps customers happy and satisfied with the website offers. This study focuses on consumer electronics and observes the comparative influence of fundamental elements (i.e., hedonic motivation, habits, perceived risk, technological trust, and technological awareness) on purchasing customer satisfaction. The study further examines the impact of customer satisfaction with online purchases with website continuance intention (WCI). Notably, this study explores the moderating effect of word-of-mouth (WOM) on the relationship between customer satisfaction with online purchases and website continuance intention. This study designed a web-based survey and recruited frequent visitors including international and citizens of Qatar for data collection. The study employed a purposive sampling technique and used three standardized psychological tools to obtain the data set needed to measure customer satisfaction with online purchases. The survey used a web link, distributed 600 questionnaires via email and social media, and received only 468 responses. After screening, only 455 were valid responses. The study showed a response rate of 75.83%. The study results showed that hedonic motivation, habits, perceived risk, and technological awareness were positively related to customer satisfaction with online purchasing. Besides, customer satisfaction with subsequent online purchases is also positively associated with website continuance intention (WCI). The results revealed that this relationship remained stronger when word-of-mouth (WOM) was higher. Hence, this shows that online shopping is seen as a vital and interesting activity in the Qatari context. The findings provide useful insights for future studies to explore the effects of COVID-19 on online purchase intentions.